PENYELESAIAN SENGKETA PROSES PEMILIHAN UMUM DI INDONESIA - Hasun, Maulana; Kunaifi, Aang; Setyadji, Sri; Hufron, Hufron (Program Pascasarjana Universitas Sunan Giri Surabaya, 2020)
One of the main pillars of democratic governance is the implementation of general elections (Elections), the Election Organization involves at least 3 (three) important actors who interact with each other, namely Election Contestants, Election organizers and citizens who hold the right to vote (Voters). In its interactive relationship in the stages of the Election process, there can be a hormonal relationship or a conflict relationship. The enactment of Law number 7 of 2017 concerning General Elections as the basis for holding simultaneous Elections in 2019. Giving authority to Bawaslu, Provincial Bawaslu and Regency / City Bawaslu in resolving disputes in the Election process, due to the issuance of KPU, provincial KPU or regency / city KPU decisions. The Bawaslu Decision is final and binding except relating to 3 (three) matters, namely verification of the Election Contesting political parties, determination of the permanent candidate list for DPR, DPD, provincial and regency / city DPRD candidates and Candidate Pairs. The Election Supervisory Body's decision in resolving election disputes is almost the same as other judicial institutions, this is seen from the character of the Election Supervisory Body's final and binding decision, the substance of the decision is almost the same as the judiciary and procedural aspects of the electoral process dispute through the trial mechanism. Seeing the legal construction of judicial authority, Bawaslu is not a judicial body, because it does not belong to the judiciary under the Supreme Court, the Constitutional Court and is not included in the special court. The authority of the PTUN in dispute over the election process can only be done, if administrative efforts to Bawaslu have been made and the decision is final and binding and no other legal efforts can be made. However, the Election Law does not mention sanctions for those who do not follow up on PTUN decisions, this can be seen in the case of Oesman Sapta Odang, the KPU finally chose to follow the Court's Decision more.